Business research methods - Blumberg, Boris F.; Cooper, Donald R.; Schindler, Pamela S. (London : McGraw-Hill Education, 2014)
Are you about to begin your dissertation or a research project, but don't know what topic to choose? Are you unsure of what research methods to use and how they should be applied to your project? Are you worried about how to write up your research project? Then this is the book for you! A balanced coverage of qualitative and quantitative methods means that no matter what approach you choose to use for your project, there are examples and case studies to help guide you through the process. Student Research boxes provide an insight into situations and research decisions that students have encountered in real life projects. They contain hints, tips and sometimes questions to help you think through your own project. A Running Case Study charts the progression of two student research projects - one qualitative and one quantitative - and shows how the content of each chapter can be used to develop their projects. Thought provoking questions are included in order to help you consider the issues and decisions involved, which you can then apply to your own project. Deeper Insight boxes delve further into particular research issues, offering you a detailed description to increase your understanding of these areas, whilst Real Life examples put research methods into context, by showing you how they have been applied in real world situations. The Online Learning Centre contains a vast amount of extra resources to help you create a superior project: six statistical chapters are available to help you prepare, test and analyse your hypotheses and data. Extra cases, appendices and dataset exercises help you to take your study further. Check out the Research Skills Centre for free chapters of Study Skills books, examples of good and bad proposals, and templates for questionnaires and surveys
Part 1: Essentials of Research 1. The Nature of Business and Management Research 2. The Research Process and Proposal 3. Literature Review 4. Ethics in Business Research Part 2: Research Methods 5. Quantitative and Qualitative Research 6. Sampling Strategies 7. Primary Data Collection with Surveys 8. Primary Data Collection: Qualitative Data 9. Secondary Data and Archival Sources 10. Content Analysis and Other Qualitative Approaches 11. Case Studies 12. Experimentation Part 3: Research Instruments 13. Fieldwork: Questionnaires and Responses 14. Measurement and Scales 15. Writing and Presenting Research Outcomes Part 4: Statistical Background (ONLINE) 16. Data Preparation and Description 17. Exploring, Displaying and Examining Data 18. Hypothesis Testing 19. Measures of Association 20. Multivariate Analysis: An Overview 21. Qualitative Data Analysis: An Overview Appendices Cases
Keywords: Business -- Research -- Methodology; Dataindsamling; Business -- Research -- Methodology